Effectiveness of Ultrasound Therapy in Cervical Myofascial Pain Syndrome: A Double Blind, Placebo-Controlled Study - Ümit Dündar,; Özlem Solak,; Fatma Şamlı,; Vural Kavuncu, (Archives of Rheumatology, 2010)
Objective: Ultrasound therapy is commonly employed in the treatment and management of soft tissue pain. The aim of this study was to investigate the effectiveness of ultrasound therapy in cervical myofascial pain syndrome (MPS). Materials and Methods: A total of 55 patients with cervical MPS were included in this study. The patients were randomly assigned into two groups. In Group 1 (n=28), ultrasound diathermy was administrated over three trigger points bilaterally for 8 minutes (min) once a day for 15 days over a period of three weeks. In Group 2 (n=27), the same treatment protocol was given, but the ultrasound instrument was switched off during applications. All patients in both groups performed daily isometric exercise and stretching exercises for the cervical region. Parameters were measured at baseline, and at weeks 4 and 12. All patients were evaluated with respect to pain (at rest and movement) and assessed by visual analog scale and active range of motion was measured using an inclinometer and a goniometer. Disability and quality of life were evaluated with the Neck Disability Index (NDI) and the Nottingham Health Profile (NHP). Results: In both groups, statistically significant improvements were detected in all outcome measures at weeks 4 and 12 (except sleep and social isolation subgroups of NHP in both groups) compared with baseline (p<0.05). However, improvement in NDI and pain and physical abilities subgroups of NHP was better in Group 1. Pain reduction evaluated with respect to pain at rest and movement was also better in Group 1. Conclusion: The results of our study showed that ultrasound therapy is effective in the management of cervical MPS. (Turk J Rheumatol 2010; 25: 110-5)